2022
DOI: 10.1001/jamaoncol.2021.6036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elective Internal Mammary Node Irradiation on Disease-Free Survival in Women With Node-Positive Breast Cancer

Abstract: IMPORTANCEThe benefit of internal mammary node irradiation (IMNI) for treatment outcomes in node-positive breast cancer is unknown.OBJECTIVE To investigate whether the inclusion of IMNI in regional nodal irradiation improves disease-free survival (DFS) in women with node-positive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 32 publications
4
69
0
Order By: Relevance
“…In KROG 08-06, a significant benefit from IMNI was found in patients with medial/central tumors for disease-free survival and breast cancer mortality. 23 This pattern was in agreement with our findings. Results from both NCIC-CTG MA.20 and KROG 08-06 suggested a more pronounced effect of nodal irradiation in patients with hormone receptor-negative disease.…”
Section: No Imnisupporting
confidence: 93%
“…In KROG 08-06, a significant benefit from IMNI was found in patients with medial/central tumors for disease-free survival and breast cancer mortality. 23 This pattern was in agreement with our findings. Results from both NCIC-CTG MA.20 and KROG 08-06 suggested a more pronounced effect of nodal irradiation in patients with hormone receptor-negative disease.…”
Section: No Imnisupporting
confidence: 93%
“…An additional study was identified by Google [ 13 ]. After the removal of duplicates and studies not meeting the inclusion criteria, seven publications reporting on five independent studies were included (see Figure 1 for the study selection schema) [ 10 , 11 , 12 , 13 , 14 , 15 , 24 ]. An additional study reported on updated toxicity, but these data were not relevant to the analysis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Individual study characteristics and details on the radiation treatment in each arm are shown in Table 1 . In three studies, the control group was treated with radiation to the regional lymph nodes other than the IMN [ 13 , 14 , 24 ] and in two studies, the control group was treated with radiation to the breast or chest wall only [ 10 , 11 ]. About half of the included women had left sided tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Study participants were stratified by N stage and surgery type. 8 Although the study found no significant effect on outcomes, regardless of whether the internal mammary nodes were radiated, an unplanned subset analysis showed inclusion of the internal mammary nodal chain resulted in a 10% improvement in disease-free survival in patients with centrally or medially located tumors (hazard ratio, 0.42; P5.03). # 2022 National Comprehensive Cancer Network, Inc. All rights reserved.…”
Section: Debates Over Rnimentioning
confidence: 85%